Impact of Working Capital Management on Financial Performance of Small Scale Business in Nakawa Division - Jacqueline Kyabishikyi (Uganda Christian University, 2024)
This research focused on effect of working capital management on the financial performance of Small and Medium Enterprises operating in Nakawa Division. The specific aim of this study was to find out the effect of working capital management on financial performance of small and medium enterprises in Nakawa division, three objectives central to it however were achieved; determination of the impact of accounts receivable on the financial performance of small and medium enterprise, review of cash management as a provider of value in small and medium enterprises and evaluation of inventory management in enhancing the financial performance of small and medium enterprises. There were 200 total employees from different small and medium businesses and the sample used was 52 respondents. A simple random sampling technique was used in this research and all the members of the finite population had equal chances of being selected because the target respondents were either non engaged or engaged individuals who possess certain knowledge regarding any financial performance of small and medium enterprises, these were of better abilities to satisfactorily address the research questions. This eliminated the adverse selection bias that could have been caused when the population under study is favored by the research. The data was collected through Questionnaires as the research tool. The inferential analysis which sought to establish the relationship among the variables showed that there was a clear positive and significant relationship between accounts receivable management and the financial performance of small and medium enterprises in Nakawa Division as well as the Cash management which has also been presented and it was established that there was and there is a positive significant association with the financial performance of Small and Medium Enterprises within Nakawa Division. And lastly was the inventory management an effective tool for this purpose that it was positively and significantly related to the financial performance of Small and Medium Enterprises with in Nakawa Division. The study went further to recommend that working capital management has an impact on the financial performance of Small and Medium Enterprises and that there is a positive significant relationship, the study recommends that Small and Medium Enterprises need to management their debts very well, management their receivables, management cash and also retention of inventory should be effectively managed so as to enhance their financial performance.
Undergraduate Research